Available Cosmos: Geoinformation Technologies for Schoolchildren - M. A. Sergeeva; M. V. Voronina; M. K. Raskladkina (Мир новой экономики)
The article presents methodical and technical developments on the use of geoinformation technologies in secondary schools and additional educational institutions. The problem in the reorganization of the training courses of the Earth sciences has long been ripe. Its origins lie in the rapid expansion of the field of application of geospatial data, in the transformation of this sphere from a highly specialized to mass and, as a consequence, the needs of the aerospace business in obtaining highly qualified, erudite professionals. The development of aerospace education entails the need to develop new types of educational courses beginning with a school bench that will raise the prestige of earth sciences, break away from boring textbooks and bring the educational program in line with the needs of the economy and with the interests and capabilities of modern students.